Y = sqrt(x/m) * sqrt(m/x)Using product rule, we getdy/dx ={ x^2 * sqrt(m/x) - m^2 * sqrt(x/m) } / 2mx^2Now, 2xy*dy/dx =(x^2 - m^2) / mxSimply substitute the value of 2xy*dy/dx in the question and solve further to get 0The final answer is 0
Track your progress, build streaks, highlight & save important lessons and more!
Y = sqrt(x/m) * sqrt(m/x)Using product rule, we getdy/dx ={ x^2 * sqrt(m/x) - m^2 * sqrt(x/m) } / 2mx^2Now, 2xy*dy/dx =(x^2 - m^2) / mxSimply substitute the value of 2xy*dy/dx in the question and solve further to get 0The final answer is 0